THE EFFECT OF PINCHING AND SPRAYING WITH ZINC ON SOME OF THE QUALITIES OF VEGETATIVE AND FRUITY GROWTH OF CASTOR PLANT (RICINUS COMMUNIS L.) - Bushra Abbas Taher; Ahmed Hassan Yassin (European Journal of Agricultural and Rural Education, 2022)
A factorial experiment was carried out according to the design of the complete random sectors (R.C.B.D.) during the spring of 2021 in agricultural fields at the University of Diyala in alluvial mixed soils to study the effect of two dates of pinching as well as the comparison treatment (non-pinching, 15, 40) days after cultivation and spraying with zinc in two concentrations with the treatment of non-spraying (300,150,0) ppm, to study their effect on some of the vegetative and fruity growth traits of the castor plant (Ricinus communis L.). The results showed the following: The process of pinching the growth tip of a plant (the first pinching) significantly exceeded the average characteristic of the dry weight of the leaves and plant (g), the number of fruits in the plant-1 and the weight of 300 seeds (g) and the yield of seeds in the plant and amounted to 68.7 g, 383.4 g, 115.7 g, 78.81 g, 53.55 g respectively,and the spraying coefficients with zinc at a concentration of 300 ppm showed significant superiority in the average quality of dry weight of the leaves and plant (g), the number of fruits of the plant, and the weight of 300 seeds (g) and amounted to 67.0 g, 374.0 g, 112.8 g, 76.66 g respectively, and the overlap between the two trial factors (the first earring with zinc spraying at a concentration of 300 ppm) had a significant effect on the characteristic of the dry weight of the leaves and plant (g), the number of fruits of the plant and the weight of 300 seeds (g) and were 72.4 g, 407.1 g, 121.9 g, 80.63 g respectively .